Identifying disruptive contingencies for catastrophic cascading failures in power systems - Zhai, Chao (2022)
Due to the evolving nature and the complicated coupling relationship of power system components, it has been a great challenge to identify the disruptive contingencies that can trigger cascading blackouts. This paper aims to develop a generic approach for identifying the initial disruptive contingencies that can result in the catastrophic cascading failures of power systems. The problem of contingency identification is formulated in the mathematical framework of hybrid differential-algebraic system, and it can be solved by the Jacobian-Free Newton-Krylov method, which allows to circumvent the Jacobian matrix and relieve the computational burden. Moreover, an efficient numerical algorithm is developed to search for the disruptive contingencies that lead to catastrophic cascading failures with the guaranteed convergence accuracy in theory. Finally, case studies are presented to demonstrate the efficacy of the proposed identification approach on the IEEE test systems by using different cascade models.